2017
DOI: 10.1111/fwb.12984
|View full text |Cite
|
Sign up to set email alerts
|

Fishpond dams affect leaf‐litter processing and associated detritivore communities along intermittent low‐order streams

Abstract: Intermittent streams are common and widespread freshwater ecosystems globally. While dams greatly affect the ecology of permanent streams, the extent of their effects on intermittent streams remains largely unknown. The physical and chemical alterations induced by dams could have particularly strong impacts on the functioning of intermittent low‐order streams, especially due to the limitations they place on colonisation of aquatic biota from downstream permanent waters. Leaf‐litter breakdown (LLB) and associat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(6 citation statements)
references
References 76 publications
0
5
0
1
Order By: Relevance
“…This hypothesis is supported by our observations since, at this site, the community was dominated by Gammarus pulex, a taxon characterised by an essentially aquatic life cycle, while the other three sites were dominated by insects known to exacerbate terrestrial phases during dry periods (Tachet et al, 2010). Nevertheless, this previous study conducted on these streams and other similar ones in this area showed that Gammarus pulex was not dominant in permanent streams without fishpond, suggesting that flow discontinuity was not the only parameter that influenced the abundance of this taxon (Four et al, 2017b).…”
Section: Macroinvertebratementioning
confidence: 62%
See 3 more Smart Citations
“…This hypothesis is supported by our observations since, at this site, the community was dominated by Gammarus pulex, a taxon characterised by an essentially aquatic life cycle, while the other three sites were dominated by insects known to exacerbate terrestrial phases during dry periods (Tachet et al, 2010). Nevertheless, this previous study conducted on these streams and other similar ones in this area showed that Gammarus pulex was not dominant in permanent streams without fishpond, suggesting that flow discontinuity was not the only parameter that influenced the abundance of this taxon (Four et al, 2017b).…”
Section: Macroinvertebratementioning
confidence: 62%
“…At downstream fishpond site the temperature was significantly higher of 1.7°C on average during the period under investigation i.e. January to April 2015 (Four et al, 2017b). However, all sampling sites were at good ecological status according to the French "water guide"SEQ-eau (MEED-French Water Agency, 2003).…”
Section: Study Sitesmentioning
confidence: 94%
See 2 more Smart Citations
“…Si de nombreux travaux universitaires (Aldomany et al, 2019, Banas et al, 2015Four et al, 2017aFour et al, et 2017bGaillard et al, 2016 ;Millot, 2015 ;Passy et al, 2012 ;Touchart & Bartout, 2020) ont permis ces dernières années de combler nombre de lacunes à l'échelle du limnosystème étang et d'introduire de nouveaux indicateurs comme le « centre thermique » (Choffel, 2019), la démarche par emboîtement d'échelles sortant du cas particulier d'un étang nécessite une approche différente et complémentaire. En effet, pour répondre aux approches emboîtées des « masses d'eau » à l'intérieur d'un bassin dit versant dans une vision fluvio-centrée, il est nécessaire de produire un équivalent limno-centré, qui ne soit pas basé sur la seule approche par « impact cumulé des retenues » (Carluer et al, 2017, Habets et al, 2018 qui est par essence même fluvio-centrée, mais appliquant une démarche hydrosystémique par « territoires de l'eau » (Bravard & Pourtier, 2003) où les dimensions longitudinales, verticales, latérales et temporelles sont étudiées à égale proportion et en ne négligeant pas l'anthroposystème (Lévêque et al, 2003) dans lequel ce territoire s'inscrit.…”
Section: Pascal Bartoutunclassified